Positive Solutions of a Kind of Equations Related to the Laplacian and p-Laplacian. (13th October 2014) - Zhang, Fangfang; Liang, Zhanping
Abstract : Positive solutions of a kind of equations related to the Laplacian andp -Laplacian on a bounded domain inR N withN ⩾ 1 are studied by using variational method. A sufficient condition of the existence of positive solutions is characterized by the eigenvalues of linear and another nonlinear eigenvalue problems.